Osteoporosis - pathophysiology, symptoms, prevention and treatment - Agnieszka Dobosz; Agnieszka Smektała (Polish Pharmaceutical Society, 2020)
Osteoporosis is a disease that leads to the weakening of bone structure and increases the possibility of bone fractures. It can affect especially an old people and the women in the postmenopausal age. The reason is the osteoclasts resorption hyperactivity in the relation to the bone forming cells. Osteoporosis can remain latent for many years and symptoms can occur in the case of fractures, most often of the vertebrae, radius bone or bonehead of the femur. In many cases, disability resulting from the development of the disease, causes depression, social withdrawal, reluctance to live and chronic pain. Osteoporosis affects about 38% of people older then 50 years,, when calcium absorption in the intestines becomes less efficient and bone mass undergoes faster resorption. In the postmenopausal age, the estrogen deficiency consists of stimulating osteoblast activity and maintaining calcium and phosphorus homeostasis in the body. Diagnosis of osteoporosis is based mainly on the densitometric BMD (Bone Mineral Density) measurement. Another diagnostic method is FRAX (Fracture Risk Assessment Tool), a 10-year fracture probability calculator. In order to take into account the risk of osteoporosis, ancillary laboratory tests such as measuring calcium levels and activ forms of vitamin D in the blood, can be used. By taking preventive action, the process of bone dissolution can be slowed down. Prophylaxis of osteoporosis affects the change in the lifestyle and diet, which must ensure adequate consumption of calcium and magnesium ions, proteins, vitamins D and K2. Deficiency of vitamin D and calcium ions leads to the activation of compensatory mechanisms in the body, which can start the osteoporosis. Magnesium ions prevent soft tissue calcification, induce bone mineralization and affect ostoblast activity. Vitamin K2 provides participation in osteocalcin synthesis and stimulates bone mineralization. The most commonly used drugs in the pharmacotherapy of osteoporosis are bisphosphonic acids, additionary with calcium and vitamin D3 supplements. Molecular mechanisms of bisphosphonic action depend on their structure, specially the length of the side chain and the presence of a nitrogen atom. Bisphosphonates should be taken on an empty stomach and the patient should not change body position for 30 minutes. The most common side effects of these drugs are diarrhea, stomach ache, reflux, indigestion and tarry stools. Other drugs used nowadays in the therapy are denosumab, strontium renalate, raloxifene and teriparatide. The aim of this work is to present the pathophysiology, symptoms, diagnostics, prevention and treatment methods of the osteoporosis. Unfortunately this disease often occurs in the society, and it is necessary to broaden the knowledge how to prevent its progression and treatment, specially at the initial stage of the disease, when the therapy gives the highest therapeutic benefit.